The New National Rankings in India - Varghese, N.V. (International Higher Education, 2018)
India started ranking its higher education institutions in 2015. Although a major share of higher education institutions in India are private, public institutions dominate the ranking list. The ranking exercise is not a substitute to improve the overall quality of the system, since a large majority of higher education institutions in India do not participate in the exercise. India needs to adopt more effective strategies to improve the overall quality of higher education, by focusing on research and teaching–learning processes at the institutional level.